Students’ Characteristics as Indicator for Effective Teaching (Sains Humanika, 2013)
Students are the most valuable asset to a country. The success of students in learning science and mathematics not only depends on how well the educators look into the students’ needs per se but also and the interactions of both parties during teaching and learning processes. Therefore, this research was carried out to gather information and to formulate the standard criteria for teaching and learning science and mathematics. The research instruments were the set of questionnaires that were designed to identify students’ abilities, background, perception, students’ interests and motivation, multiple intelligents, thinking styles, learning style and creativity on teaching and learning science and mathematics. The respondent consists of 101 second year and 104 third year students who have taken science and mathematics programs. The research found out that there are interesting patterns of students’ performance according to their characteristics. Finally, the findings revealed that there are challenges for the science and mathematics educator to make use students’ characteristics to promote optimum learning among students.
Keywords: Teaching science and mathematics